DIFFERENT METHODS OF LEARNING (Ustozlar uchun, 2025)
This article explores the various methods of learning used in modern education. It examines traditional approaches, such as lecture-based and textbook learning, as well as contemporary methods, including collaborative learning, experiential learning, and e-learning. The study highlights the advantages and challenges of each method, emphasizing how different approaches can be applied to improve student engagement, understanding, and skill development. By analyzing the effectiveness of multiple learning strategies, the article provides insights for educators to select and combine methods that best suit their students’ needs and learning objectives.